396 PREVALENCE OF OVERWEIGHT AMONG ADOLESCENTS IN RURAL CALIFORNIA. (1st January 2006) - Shaikh, U.; Byrd, R. S.; Franks, P.
Abstract : Background: The nationwide prevalence of adolescent overweight is 16%. The prevalence of overweight and its contributing factors has been extensively studied in urban youth. It is believed that urban adolescents are exposed to an obesogenic environment that results in excessive caloric intake and sedentary activities. There is little information on the prevalence of and risk factors for overweight in adolescents in rural communities. The purpose of this study was to determine the prevalence of adolescent overweight in rural California and to determine related environmental factors. Methods: We used the California Health Interview Survey (CHIS) 2003 adolescent survey public use file in data analysis. The CHIS is a telephone survey utilizing random digit dialing and a stratified random sampling design. The response rate for the CHIS 2003 adolescent survey was 57.3%. A total of 4, 010 adolescents were surveyed and survey weights were used for population estimations. We utilized the operational definition of urban/rural from the California Rural Health Policy Council and classified adolescents with body mass indices ≥ 95th percentile for age and gender as overweight. Results: The overall prevalence of adolescent overweight in California is 12.4%. Adolescent overweight is more prevalent in rural areas (16.4%) compared to urban areas (11.9%), a relationship that persisted after controlling for gender, race, parental education, and poverty level. Compared to overweight urban adolescents, overweight rural adolescents were more likely to be male, white, have safe play areas further from home, and have a lower likelihood of discussing nutrition and moods/emotions with their health care provider at their last physical examination. Discussion: Adolescent overweight is more prevalent in rural than in urban areas of California. Rural youth may face special circumstances that affect implementation and success of interventions. Some of these may be access to prevention and treatment services, travel distances to health care providers, limited resources, and physical activity opportunities. Interventions need to consider these unique challenges of rural youth.